Protective effects of defatted dabai peel extracts in hypercholesterolemic rabbits based on histopathological methods - Khoo, Hock Eng; Azlan, Azrina; Ismail, Amin; Al-Sheraji, Sadek Hassan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Defatted dabai peel contains a high amount of anthocyanin. Anthocyanins are known to prevent several types of disease, including cardiovascular-related complications. This study aimed to describe the effects of different doses of defatted dabai peel extract by histopathological analyses on lesions in the liver, kidney, heart and aorta. Histopathology methods were applied to determine the protective effects of defatted dabai peel extracts against hypercholesterolemia-induced oxidative damages to animal organs. Haematoxylin and eosin staining was applied for histopathology examination for liver, kidney, heart and aorta. Data showed that a high dose of defatted dabai extract (3000 mg per day) applied to hypercholesterolemic rabbits for eight weeks had mild protective effect, especially reducing the severity of hepatic fibrosis and steatosis of the renal medulla. The high dose of extract supplementation also reduced inflammation of aorta and formation of atherosclerosis plaque in the cell wall of right ventricle of the heart. The high dose of defatted dabai peel extract could be a protective agent against oxidative stress.